2020
DOI: 10.1007/s11573-020-00992-0
|View full text |Cite
|
Sign up to set email alerts
|

Cash, non-cash, or mix? Gender matters! The impact of monetary, non-monetary, and mixed incentives on performance

Abstract: Standard economic theory asserts that cash incentives are always better than non-cash ones, or at least not worse. This study employs a real effort experiment to analyze the impact of monetary, non-monetary, and a combination of monetary and non-monetary incentives on performance, where non-monetary incentives are defined as tangible incentives with market value. Our overall results suggest that there exists no significant difference in performance in response to monetary, non-monetary, and mixed incentives. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
(99 reference statements)
0
6
2
1
Order By: Relevance
“…The current study has confirmed the significance of nonmonetary motives on performance among employees with different cultural values. Nonetheless, previous studies (Hammermann and Mohnen, 2014;Sittenthaler and Mohnen, 2020) have also demonstrated the significance of both monetary and mix incentives method on employees. Accordingly, the study believes that human resource managers should not focus on solely using monetary or nonmonetary motives in their quest to motivate the employees.…”
Section: Conclusion Implications and Limitations 61 Implicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…The current study has confirmed the significance of nonmonetary motives on performance among employees with different cultural values. Nonetheless, previous studies (Hammermann and Mohnen, 2014;Sittenthaler and Mohnen, 2020) have also demonstrated the significance of both monetary and mix incentives method on employees. Accordingly, the study believes that human resource managers should not focus on solely using monetary or nonmonetary motives in their quest to motivate the employees.…”
Section: Conclusion Implications and Limitations 61 Implicationsmentioning
confidence: 94%
“…Nonmonetary motives have motivational properties inherent in them, highly visible and can be evaluated independently of other income (Sittenthaler and Mohnen, 2020). Previous studies (Brunetto et al , 2017; Jeffrey, 2009; Sittenthaler and Mohnen, 2020) demonstrated the effectiveness of nonmonetary motives on performance. According to Redmond and Sharafizad, nonmonetary factors increase discretionary effort and performance.…”
Section: Theoretical Review and Hypothesismentioning
confidence: 99%
“…Many businesses and organizations use a variety of incentives or rewards to motivate staff to improve their performance (Sittenthaler and Mohnen, 2020 ). Reward can also be defined as a variety of one-of-a-kind advantages delivered to employees as a substitute for effort or non-trivial monetary value (Choi and Presslee, 2020 ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Since improving patient satisfaction is also beneficial to the hospital itself, hospitals also encourage medical staff to improve patient satisfaction through their own human resource policies. However, whether he monetary incentives would enhance physicians’ job performance in terms of patient satisfaction is still unknown [ 8 , 9 ]. One of the core dilemmas is whether monetary incentives are a good choice.…”
Section: Introductionmentioning
confidence: 99%